Microalgal (Nannochloropsis sp., Isochrysis sp. and Tetraselmis sp.) diet for spat of the green mussel (Perna viridis) in Bangladesh: growth, filtration and ingestion efficiency - Zahidul Islam; Jakia Hasan; Turabur Rahman; Md. Aktaruzzaman; Shafiqur Rahman; Mohosena Begum Tanu (Discover Food)
Abstract Green mussel aquaculture is increasing day by day and mostly relies on natural spat collection, but some hatchery-produced spat is also employed. Nevertheless, the use of hatchery spat may be more convenient when they are produced with adequate feed in a controlled environment where quality is ensured with maximum survival. So, this study was designed for 45 days to determine the efficacy and suitability of indigenous microalgae (Nannochloropsis sp., Isochrysis sp. and Tetraselmis sp.) as feed for Perna viridis spat production in hatchery conditions. The result shows the highest mean survival rate in the Isochrysis sp. fed spat (71.33 ± 1.52%), which differs significantly among the dietary treatments. In addition, the survival rate was found to be 61.67 ± 7.57% in Tetraselmis sp. fed spat and 55.33 ± 5.86% in Nannochlpropsis sp. fed larvae. In the case of filtration and ingestion rate, Tetraselmis sp. fed spat had the highest filtration rate of 0.997 ± 0.02 mL/spat/h, whereas Nannochlorpsis sp. fed spat had the highest ingestion rate of 7.99 × 106 ± 1.16 cells/spat/h. In the case of growth, spat fed with Isochrysis had higher shell weight (0.23 ± 0.014 g), length (9.53 ± 0.34 mm), width (4.73 ± 0.22 mm) and depth (2.08 ± 0.05 mm) where the Nannochloropsis sp. diet showed the lowest growth. However, the data were not significantly different from each other in the case of shell width and depth. Similarly, spat fed with Isochrysis sp. had a higher instantaneous relative growth rate (0.00541 ± 0.0007 µm/day) than the other two species. The result of the study showed enhanced growth with Isochrysis sp. fed larvae. The findings will provide a better understanding of appropriate food selection in green mussel spat to improve their production in captivity.